Toroidal ferroelectricity in perovskite nanoparticles. (1st April 2017) - Dudhe, C.M.; Khambadkar, S.J.; Dhoke, N.V.
Abstract: Now-a-days, a novel concept of toroidal ferroelectricity is at the center of interest of many researchers. However, fundamental information of toroidal ferroelectricity is limited. In the present paper some novel thoughts regarding the same were illustrated on the basis of experimental evidences of domain structures in Pb0.99 TiO3 :La0.01 and KNbO3 nanoparticles. Additional oxygen uptake in the structure seems to be a possible source of toroidal ferroelectricity. We observed a few novel toroidal geometries in Pb0.99 TiO3 :La0.01 nanoparticles. It was concluded that, the toroidal electric dipole moment collapses to zero under some circumstances and gives rise to conditions suitable for the regular ferroelectricity. Graphical abstract: